Finding the back of the net: Networks and migrant recruitment in Norwegian football - Elliott, R.; Gusterud, E. (International Review for the Sociology of Sport, 2018)
The intention of this paper is to analyse the role that networks play in enabling the recruitment of a group of male migrant professional footballers employed by clubs based in Norway`s top professional football league - the Tippeligaen. Based upon a series of semi-structured interviews conducted with migrants and recruiters, and synthesising concepts derived from the sociology of sport and the broader study of migration, the analysis identifies that the recruitment of migrant workers to Tippeligaen clubs reflects a mix of both formal and informal processes. Whilst agents operate as key actors in the mobilisation of foreign labour, the analysis shows how recruitments in this particular athletic context are also dependent on processes of human mediation facilitated by a series of informal interdependent networks of relationships.